2013
DOI: 10.1108/13595471311315074
|View full text |Cite
|
Sign up to set email alerts
|

Using the Mental Capacity Act in complex cases

Abstract: Purpose -The purpose of this paper is to explore the way that practitioners apply the 2005 Mental Capacity Act (MCA) in complex cases involving people with learning disabilities who cannot make some key decisions by themselves. Like many qualitative studies it began with a felt sense that practitioners were struggling to apply the clear framework set out in the Act to real life situations, and that some of the decisions they were faced with did not fit neatly into the linear, cognitive model of decision making… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 4 publications
(5 reference statements)
0
11
0
Order By: Relevance
“…Yet, worryingly, a report published 6 years after the introduction of the MCA, which explored the premature deaths of those with an intellectual disability, found that decisions were often made by one person, rather than the multidisciplinary group approach, which is advocated in the MCA. 35 Furthermore, Heslop et al 10 and Taylor 11 found that health care professionals' decisions were influenced by prejudice and personal views and based on what they felt was the appropriate decision to be made. This was combined with a lack of information about the patient and family, which is required in order to achieve a truly holistic review.…”
Section: Best Interestsmentioning
confidence: 99%
“…Yet, worryingly, a report published 6 years after the introduction of the MCA, which explored the premature deaths of those with an intellectual disability, found that decisions were often made by one person, rather than the multidisciplinary group approach, which is advocated in the MCA. 35 Furthermore, Heslop et al 10 and Taylor 11 found that health care professionals' decisions were influenced by prejudice and personal views and based on what they felt was the appropriate decision to be made. This was combined with a lack of information about the patient and family, which is required in order to achieve a truly holistic review.…”
Section: Best Interestsmentioning
confidence: 99%
“…John developed very rigid drinking behaviours and would not contemplate any alternative that would cause him to spend more money than he did, despite being financially secure. An audit of complex cases conducted by the UK's Office of the Public Guardianthe body responsible for administrating the MCAsuggested autistic intransigence could impair a person's capacity (Brown and Marchant, 2013). How should mental capacity assessments account for autistic rigidity of thought when it is pertinent to the decision being assessed?…”
Section: Assessing Mental Capacitymentioning
confidence: 99%
“…Additionally, standardised capacity assessments do not take into account the impact of emotional state on decision-making (Beadle- Brown, 2015). Within the MCA guidance, the examples of assessments place emphasis on making information available, rather than assessing real-life, dynamic situations (Brown and Marchant, 2013). Thus, when the individual steps out of this structured environment, and is required to make complex multi-faceted decisions that may have an emotional component, problems may arise which may affect their safety and wellbeing (Brown and Marchant, 2013).…”
mentioning
confidence: 99%
“…Within the MCA guidance, the examples of assessments place emphasis on making information available, rather than assessing real-life, dynamic situations (Brown and Marchant, 2013). Thus, when the individual steps out of this structured environment, and is required to make complex multi-faceted decisions that may have an emotional component, problems may arise which may affect their safety and wellbeing (Brown and Marchant, 2013). The implementation of the MCA and assessment in this way can lead to wrongful assumptions of capacity that leave survivors in vulnerable situations without appropriate support and safeguarding in place (George and Gilbert, 2018).…”
mentioning
confidence: 99%